The regulation of autophagy by calcium signals: Do we have a consensus?. (March 2018) - Bootman, Martin D.; Chehab, Tala; Bultynck, Geert; Parys, Jan B.; Rietdorf, Katja
Graphical abstract: Highlights: Calcium (Ca 2+ ) has been shown to control various stages of autophagic flux. Cytosolic Ca 2+ signals can trigger autophagy, but can also inhibit autophagy too. Different Ca 2+ channels and Ca 2+ sources have been shown to impinge on autophagy. Buffering cytosolic Ca 2+ with BAPTA blocks induction of autophagy by almost any means, indicating that Ca 2+ signalling is essential. Autophagy and apoptosis share many of the same Ca 2+ signalling toolkit components. Abstract: Macroautophagy (hereafter called 'autophagy') is a cellular process for degrading and recycling cellular constituents, and for maintenance of cell function. Autophagy initiates via vesicular engulfment of cellular materials and culminates in their degradation via lysosomal hydrolases, with the whole process often being termed 'autophagic flux'. Autophagy is a multi-step pathway requiring the interplay of numerous scaffolding and signalling molecules. In particular, orthologs of the family of ∼30 autophagy-regulating (Atg) proteins that were first characterised in yeast play essential roles in the initiation and processing of autophagic vesicles in mammalian cells. The serine/threonine kinase mTOR (mechanistic target of rapamycin) is a master regulator of the canonical autophagic response of cells to nutrient starvation. In addition, AMP-activated protein kinase (AMPK), which is a key sensor of cellular energy status, can trigger autophagy by inhibiting mTOR, or by phosphorylating other downstream targets. Calcium (Ca 2+ ) has been implicated in autophagic signalling pathways encompassing both mTOR and AMPK, as well as in autophagy seemingly not involving these kinases. Numerous studies have shown that cytosolic Ca 2+ signals can trigger autophagy. Moreover, introduction of an exogenous chelator to prevent cytosolic Ca 2+ signals inhibits autophagy in response to many different stimuli, with suggestions that buffering Ca 2+ affects not only the triggering of autophagy, but also proximal and distal steps during autophagic flux. Observations such as these indicate that Ca 2+ plays an essential role as a pro-autophagic signal. However, cellular Ca 2+ signals can exert anti-autophagic actions too. For example, Ca 2+ channel blockers induce autophagy due to the loss of autophagy-suppressing Ca 2+ signals. In addition, the sequestration of Ca 2+ by mitochondria during physiological signalling appears necessary to maintain cellular bio-energetics, thereby suppressing AMPK-dependent autophagy. This article attempts to provide an integrated overview of the evidence for the proposed roles of various Ca 2+ signals, Ca 2+ channels and Ca 2+ sources in controlling autophagic flux.